VAGINAL METASTASIS OF CHORIOCARCINOMA IN A 3O YEAR OLD FEMALE INITIALLY DIAGNOSED AS UTERINE PROLAPSE. (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2020)
Introduction: Vaginal metastasis in choriocarcinoma complicates about 30% of patients with  choriocarcinoma. The commonest site of metastatic is the lungs and is seen in a majority of patients with  choriocarcinoma.  Vaginal metastasis of choriocarcinoma can be misleading at the time of presentation resulting in  misdiagnosis and delay in initiation of life saving treatment.  The case is presented of a 30-year-old, para1+1 with history of a slow growing, painful and easily bleeding  vaginal mass that was initially thought to be uterine prolapse or a prolapsed leiomyoma.